Air-rail intermodality from airlines' perspective - Givoni, M (Inderscience Publishers, 2007)
Airlines can benefit from air-rail substitution, provided it is done under cooperation and not competition, between the airlines and the railways. Such cooperation should lead to airline and railway integration, a concept the paper introduces and examines for the case of London Heathrow airport (LHR). Analysis of the benefits to airlines and mainly British Airways (BA) is described leading to the conclusion that airlines and the air transport industry in general, should vocally support the development of the railway network in order to ensure that this network includes stops at the major airports.